Acute kidney failure and extramedullary lung infiltration as the initial presentation of multiple myeloma: A case report - Rabrenović, Violeta; Nikolić, Bojan; Rabrenović, Milorad; Petrović, Milica; Milojević, Ana; Škuletić, Vesna; Živojinović, Dragan; Dulović, Dragan; Stojisavljević, Marko; Mirosavljević, Svetlana; Ristić, Saša; Pantović, Miloje; et al. (Vojnosanitetski pregled, 2021)
Introduction. Kidney failure in multiple myeloma is sometimes initial symptomatology and a very serious complication with an unfavorable effect on the course and prognosis of the disease. Multiple myeloma is a disease characterized by the proliferation of plasmocytes in the bone marrow, and in rare cases, it can be extramedullary in various organs and systems. Pulmonary plasmacytoma localization is a rare extramedullary localization, especially when it represents one of the initial manifestations of multiple myeloma. Case report. We present a patient with progressive acute kidney failure who has started hemodialysis treatment. On chest radiography, a homogeneous shadow was observed along the left chest wall, and the multislice computed tomography (MSCT) pointed to the tumor formation in the pulmonary parenchyma in the projection of the left upper pulmonary lobe with signs of pleural infiltration, intercostal muscles, and V rib destruction. Laboratory examination indicated the presence of Bence-Jones proteinuria in the urine sample in addition to anemia syndrome and azotemia with hyperuricemia. After bronchoscopy and needle biopsy, diffuse infiltration of mature plasma cells was demonstrated in the cytological and histopathological findings of the lungs. The histopathological finding of bone marrow biopsy indicated multiple myeloma of Lambda type with infiltration of plasma cells – about 70%. The hematologist determined a diagnosis of multiple myeloma BJ lambda III BCS, with extramedullary lung infiltration and acute kidney failure. Further treatment was continued according to the hematological protocol while performing intermittent hemodialysis. Conclusion. Sometimes, extremely rarely, and in completely asymptomatic patients with massive pulmonary infiltration observed initially, the differential diagnosis may also represent an extramedullary presentation of multiple myeloma, which should be considered.